Assessment of green and chemically synthesized copper oxide nanoparticles against hepatocellular carcinoma - Fakhar-E-Alam M; Shafiq Zahra; Mahmood Arslan; Atif M; Anwar Hafeez; Hanif Atif; Yaqub Nafeesah; Farooq WA; Fatehmulla Amanullah; Ahmad Shafiq; Abd Elgawad Abd Elatty E; Alimgeer KS; et al. (ELSEVIER, 2022)
Copper oxide nanoparticle (CuO-NPs) attracts the attentions of human beings due to unique physicochemical and biological properties. The chemical and green synthesis approaches were used to synthesis of CuO-NPs and plant leaves extract Azadirachta indica (A. indica) was preferred in green synthesis approach. The XRD analysis was used to analyze the monoclinic crystal structure and calculate the average crystallite size in the range of 15 ti 16 nm. While, the information about different rotational and vibrational modes attached on the spectrum of CuO-NPs was identified by FTIR. After that the UV-VIS analysis provided the information about the absorbance spectrums in the range of 235 and 220 nm. The MTT assay was perfomed to investigate liver carcinoma (HepG2 cells) interaction and absorbance of CuO-NPs towards mentioned cell lines were recorded and loss in HepG2 cells viability. In an overall assessment, anticancer response of comparative study of CuO-NPs towards liver carcinoma treatment contributes significantly after successful demonstration of essential steps of suggested experimental study. Finally, comparative study of experimental and mathematical modeling of anticancer activity towards normal and liver cancer cell lines were conducted and investigated. (c) 2021 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).